pengungkapan kegembiraan pada anak 3-5 tahun dalam kajian psikolinguistik - pujihastuti, etin; rochwidjatini, rochwidjatini; lelono, bambang; hariyanti, sri nani (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2017)
In a psycholinguistic study, children at the age of 3-5 years old are considered at a differentiation period. In this period, children have already acquired their mother tongue, in terms of adultâs basic grammatical laws. The language which function as a means of communication starts working. Their vocabularies are quantitatively and qualitatively growing as their perceptions and experiences upon the world start to share with others including their expressions of feelings, in this case, their hillarious expression disclosure. However, in this period, children have not completely acquired adultsâ linguistic structures. Thus, it is that estimated there are some differences between childrenâs hilarious expression structural dislosure and adultsâ. In addition, hilarious expression structural incompleteness may result in adultsâ error perceptions on what the children mean. Based on data analysis, it is shown that children at the age of 3-5 years old have already aquired various linguistic aspects on hilarious expressions, including phonological, morphological, and syntactical aspects. one factor encouraging children to show their hilarious expressions is achievement, such as when accepted as a friend, given a gift/surprise, finding something, and feeling capable of doing something.